The Role of Epigenetic Modifications in Systemic Sclerosis: A Druggable Target - Henderson, John; Distler, Jörg; O'Reilly, Steven (Trends in Molecular Medicine, 2019)
Systemic sclerosis (SSc) is a rare autoimmune disorder characterised by skin fibrosis that often also affects internal organs, eventually resulting in mortality. Although managementof thesymptomshas extendedlifespan, patients stillsuffer from poor quality of life, hence the need for improved therapies. Development of efficacious treatments has been stymied by the unknown aetiology, although recent advancements suggest a potentially key role for epigenetics-the regulation of geneexpression by noncoding RNAs and chemical modifications to DNA or DNA-associated proteins. Herein, the evidence implicating epigenetics in the pathogenesis of SSc is discussed with an emphasis on the therapeutic potential this introduces to the field-particularly the repurposing of epigenetic targeting cancer therapeutics and newly emerging miRNA-based strategies.
CRIS-Team WoS Importer:2019-05-09